Strategic orientations of the organization - entrepreneurial, market and organizational learning - Krzakiewicz Kazimierz; Cyfert Szymon (Management)
The underlying assumption of this study is that it is possible to define some principles of strategic management. These principles, called strategic orientations, influence and direct the activities of an organisation and are intended to ensure its viability and superior performance. So far, studies into strategic orientations that set out to explain different levels of organisational performance prove that each type of strategic orientation can have a positive impact on business performance.